The Factors Affecting Demand for Alcoholic Beverage in Thailand - Pukahuta, Penporn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research objective is to study the factors affecting demand for alcoholic beverane in Thailand taken from secondary data from January 2000 to May 2013 for reference. Estimate of Multiple Regression with the method of Ordinary Least Square (OLS) is applied for statistical analysis. The research found that the amount of alcohol consumption in Thailand is related to the price of complementary goods. While the price of alcohol, average income per capita, the minimum wage, the total number of alcohol consumers, and the taxation revenue from selling alcohol beverage including taxation, limited of selling time alcohol advertising censor department, customer’s age over (18 years old), and the risk of alcohol campaigning is controlled by government policy and the place of distribution have no relation to the amount of alcohol consumption in Thailand at the significance level at 0.05. This could be mostly caused by drinkers who want to get accepted by particular group. Also, they are influenced by friends or the behavior of their parents who usually drink alcohol in a normal situation. Moreover, the advertisements with alcohol content is so appealing that the consumers want to try alcohol products. Although the government has taken further steps to control alcohol access and to set the regulations on purchasing limit, it cannot reduce the demand for alcohol consumption, because it is just a mild policy that helps to control the number of alcohol consumers, both individual and groups. It is not a regulation to stop drinking alcohol beverage. Thus, the government should implement stronger penalties than usual.